Correlation of Knee Osteoarthritis Patients' Characteristics and the Results of 30-Second Sit-to-Stand Test with Quality of Life - Susanti Dharmmika; Satryo Waspodo; Ami Rachmi; Sigit Gunarto; Fatimah Az Zakiyah; Syachla Dhiena Qothrunnada; Ayyas Robbani; Nabila Zulfa Alfina (Global Medical & Health Communication (GMHC), 2022)
Pain, joint stiffness, and difficulty performing activities like rising from sitting to standing are signs and symptoms of knee osteoarthritis (OA). These conditions are risk factors for limited mobility and lower quality of life. Knee OA is closely associated with age, women, obesity, and other characteristics. The study's objectives were to determine the correlation of knee OA patients' characteristics with functional mobility using the 30-second sit-to-stand test (30STS) and the correlation of functional mobility with quality of life using the Western Ontario and McMaster Universities Osteoarthritis (WOMAC) Index. The research method was descriptive-analytic cross-sectional using medical records of 73 knee OA patients at the Medical Rehabilitation Clinic at Soreang Hospital, Muhammadiyah Hospital, Al Islam Hospital, Al-Ihsan Regional General Hospital West Java Province, Bandung, from March until August 2021. Patients' characteristics such as age (p=0.02), onset (p=0.01), OA grade (p=0,03), and knee deformity (p=0.04 ) have a negative correlation with functional mobility based on 30STS as well as functional mobility had a negative correlation with various aspects of quality of life, such as pain (p=0.03), stiffness (p=0.02), and functional limitation (p=0.00) subscales based on WOMAC index. Age, the onset of disease, OA grade, and knee deformity significantly correlate to functional immobility. Based on the WOMAC index, functional immobility correlates with the patient's quality of life.